Mechanisms of inequalities in health and safety : conceptual model and research agenda - Stephanie Premji (Perspectives Interdisciplinaires sur le Travail et la Santé)
A growing number of studies from industrialized countries have documented elevated rates of occupational injuries and illnesses for foreign-born workers relative to their native counterparts. However, the mechanisms at play remain poorly understood. We propose a conceptual model of the mechanisms that underlie the observed inequalities. We describe how language barriers, cultural differences, vulnerable legal status, precarious economic status, newness in the host country and job, lower education and skill levels, and discrimination all generate vulnerabilities that are embodied as poor working conditions, limited knowledge of health and safety, impeded communication with employers and service providers, detrimental behaviours towards risks or health, and constrained agency. These processes, in turn, engender inequalities in exposures as well as in prevention, care, compensation and rehabilitation, which impact health. We note that in-depth information is lacking on pathways to inequalities, on how they differ by gender and ethnicity, and on how they are shaped by broader social, economic, political and legal structures. We also note the lack of information on strategies to reduce inequalities. We propose avenues for research that have the potential to lead to meaningful and actionable results.